TEATR ORQALI UMUMTA’LIM, OLIY TA’LIM MUASSASI TALABALARINI MA’NAVIY-AXLOQIY TARBIYALASHNING RIVOJLANISH HOLATI - Qalandarov, U.E. (SCIENCE and SOCIETY, 2025)
This article discusses the issues of moral and ethical education of students in general and higher education institutions through the means of theater arts, based on philosophical, pedagogical, and psychological literature. The role of theater art in developing students’ creative potential, forming their teamwork communication skills, and providing aesthetic education is analyzed.
Keywords: theater art; moral education; spiritual development; aesthetic education; creative potential; collective communication; theater pedagogy; actor’s psychotechnics; stage movement; theater technologies